Re-evaluating Io’s volcanic heat flow: critical limitations in Juno/JIRAM M-band analysis - Tosi, Federico; Mura, Alessandro; Zambon, Francesca (Frontiers in Astronomy and Space Sciences, 2025)
Understanding Io’s volcanic heat flow distribution is critical to constraining its internal structure and tidal heating mechanisms, including the debated presence of a global magma ocean. Recent analyses based on Juno/JIRAM M-band data suggest latitudinal variations in thermal emission consistent with magma ocean models. We critically assess these conclusions by addressing three key limitations in the JIRAM M-band dataset and its interpretation. First, we note that saturation effects in the JIRAM M-band imager detector, if not discussed and treated in detail, may systematically underestimate radiance from Io’s hot spots. Cross-calibration with JIRAM spectrometer data reveals non-linearity above certain values, which argues for double checking with spectrometer data whenever possible. Second, we show that using M-band integrated radiance as a direct proxy for total thermal emission is physically inconsistent without independent temperature constraints, as the spectral-to-total radiance ratio varies strongly with temperature. Reliance on M-band data alone introduces systematic biases in estimating total power outputs and spatial heat flow distributions. Third, rigorous statistical testing finds no robust correlation between latitude and spectral radiance density across multiple binning schemes. The observed latitudinal trends are highly sensitive to model-informed thresholds and dominated by a small number of bright hot spots, indicating insufficient empirical support for claimed polar heat flux asymmetries. Taken together, these findings caution against overinterpreting JIRAM M-band data in isolation and highlight the need for multi-wavelength, multi-instrument analyses with transparent data treatment to robustly constrain Io’s volcanic heat flow and internal heating models. We recommend future studies incorporate comprehensive spectral data and explicitly account for detector saturation and temperature effects to improve the physical reliability of volcanic power estimates on Io.